THE ANALYSIS OF INDONESIAN LAW TO LEGALITY TRANSACTIONS USING VIRTUAL CURRENCY OR BITCOIN - ZULKI ZULKIFLI NOOR (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Bitcoin is a series of programming codes which are then secured using cryptography which is used by certain communities as a means of payment. In economics the use of virtual currencies or bitcoin is prohibited by law, but in practice these transactions are widely used. Therefore the following problems arise, what is the position of the virtual currency (Bitcoin) in buying and selling transactions in Indonesian law and how the legal consequences of buying and selling transactions using virtual currency (Bitcoin), as well as how efforts can be made by Bank Indonesia and the Authority Financial Services for buying and selling transactions using virtual currency (Bitcoin). This research method uses descriptive analytical research method with normative juridical approach. The research data uses secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is a qualitative-juridical approach. The purpose of this study is to examine the legality of the use of virtual currencies namely Bitcoin as a means of payment in Indonesia which according to the law is not exactly said to be a currency or an object (barter) but is an information system that has properties such as money, the implementation of the Bitcoin system and its use in Indonesia is also not in line with the law. Bitcoin should not be operated and followed up on every transaction.